Pharmacokinetic study of eight bioactive components following oral administration of Zhiqiao Gancao decoction and observation of its clinical efficacy. (27th November 2019) - Shen, Xiaofeng; Li, Ling; Ma, Qihan; Chen, Hua; Wang, Jiangping; Lv, Lei; Li, Yuwei
Abstract: Zhiqiao Gancao (ZQGC) decoction is widely used in China due to its therapeutic effect on lumbar disc herniation (LDH). In this study, we compared the clinical therapeutic effects among oral ZQGC decoction treatment, bed rest, and oral anti‐inflammatory drug celecoxib treatment using visual analog scale, Oswestry Disability Index, and MacNab scores. The results showed that ZQGC decoction can significantly improve the symptoms of patients with LDH. A selective, sensitive, and rapid ultra‐performance liquid chromatography–tandem mass spectrometry method was developed and validated for the determination of eight bioactive components in rat plasma. The plasma samples were extracted by simple protein precipitation with methanol. The protonated analytes were quantitated simultaneously in positive and negative ion modes by multiple reaction monitoring with a mass spectrometer. The calibration curve of eight components in plasma showed good linearity ( r > .996) and the extraction recovery was 81.19% ± 2.15% − 100.39 ± 3.36 (relative standard deviation: 1.21%–10.70%). The accuracy of all the lower limit of quantitation values was quantified within 80%–120%, and the precision was less than 15%. This validated method was successfully applied to the pharmacokinetics study in rat plasma after ZQGC decoction oral treatment. Our research can provide experimental basis for the rational clinical application of ZQGC decoction in the treatment of LDH.